How Do Prospective Teachers Argue in Focus Group Discussion? Toulmin's Argumentation Study - Maulyda, Mohammad Archi; Fauzi, Asri; Supriadi, Supriadi; Erfan, Muhammad; Budiharjo, Anton (Universitas Islam Negeri Raden Intan Lampung, 2021)
Students’ argumentation ability is necessary for education today, which emphasizes the student-centered learning process. One way to see students’ argumentation ability is by having a discussion. Therefore, this study aimed to describe the Toulmin argumentation process for students during focus group discussions (FGD). This research is qualitative. The data collection instrument used was an open-ended questionnaire assisted by Google Form that contained common problems of the distance learning process during a pandemic. The subjects of this study consisted of fifty students from the University of Mataram. The results showed that the argumentation process was divided into three categories. The first category was the one-sentence argument. There were 58 %, or 29 students, who belonged in this category. The second category was the two sentences argument. There are 30 %, or 15 students belonged in this category. Lastly, 12 % or six students belonged to the more than three sentence argument category. The results of this study indicated that many students could not provide complete arguments. Thus, the role of lecturers is significant to improve students’ ability in providing complete argumentations. Therefore, the researchers suggest that lecturers should apply learning models that invite students to argue and discuss.